Pengaruh Temperatur PWHT Terhadap Struktur Mikro, Uji Kekerasan Dan Uji Tarik Pada Proses Pengelasan Gas Metal Arc Welding (GMAW) Aluminium 5083 - Adhi Novianto; Ipick Setiawan; Agus Pramono (Jurnal Teknik Mesin, 2020)
PWHT (Post Weld Heat Treatment) is one way to improve microstructure changes and can increase the tensile strength and hardness of the welding process. The purpose of this study was to determine changes in microstructure, hardness values, and tensile test values ​​with temperature variations of PWHT and without PWHT. The finished metal is then given a PWHT temperature variation on aluminum alloy 5083 with a temperature variation of 150 ° C, 250 ° C, 350 ° C with a heating rate of 100 ° C and heating of 80 ° C for 1 hour and a holding time of 1 hour according to The variation that has been set is continued with cooling 30 ° C for 8 hours of natural cooling in the chamber furnace machine. The results of this study indicate that changes in the microstructure due to the higher temperature of the PWHT process will reduce the concentration of porosity formed, which has a correlation with the resulting tensile strength. For the results of the tensile strength from the process without PWHT using temperature variations, the PWHT process has increased for that by doing this PWHT process greatly affects the tensile strength. The highest tensile strength is at the PWHT temperature variation of 350 ° C (263.65 MPa) compared to specimens without PWHT (253.52 MPa). Meanwhile, the hardness value is not very influential by using temperature variations of PWHT or without PWHT, the hardness value using temperature variations of PWHT 150 and without PWHT in the weld metal area (74.4 HV).